THE CONCEPT OF CREOLIZATION AND ITS ROLE IN MEDIA STUDIES (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article analyzes the theoretical foundations of the notion of creolization and its relevance in modern media studies. In creolation media texts, verbal and nonverbal elements are seen as a complex communicative process that occurs through the combination of text, image, sound, graphics, and multimedia elements. The research reveals the mechanisms by which media products, creole media, digital platforms, and social networks influence audiences. It also highlights the role of creolation in the speed of information processing, interpretation of meaning, and enhancement of emotional impact.